Solvent-Free Aza-Michael Addition of 4-Phenylurazole to α,β-Unsaturated Esters - Gholamhassan, Imanzadeh; Hemayat, Hooshmand (Letters in Organic Chemistry, 2015)
A new series of 1,2-disubstituted 4-phenylurazoles have been synthesized with aza-Michael addition of 4-phenylurazole and different acrylic esters. It was found that, without basic media, no reaction took place and the reactions proceeded easily in tetrabutylammonium bromide (TBAB), an ionic organic salt, under solvent-free conditions. The reactions were performed efficiently using 1,4- diaza-bicyclo[2,2,2]octane (DABCO), as an inexpensive base, at 60°C and produced the desired Michael adducts in good yields within 30-40 min. Surprisingly, no mono-Michael adducts were produced and bis-michael adducts were the only products of the reactions.
Keywords: 4-phenylurazole